Parathyroid hormone and physical exercise: A brief review - Bouassida, A.; Latiri, I.; Bouassida, S.; Zalleg, D.; Zaouali, M.; Feki, Y.; Gharbi, N.; Zbidi, A.; Tabka, Z. (Journal of Sports Science & Medicine, 2006)
Parathyroid hormone (PTH) is the major hormone regulating calcium metabolism and is involved in both catabolic and anabolic actions on bone. Intermittent PTH exposure can stimulate bone formation and bone mass when PTH has been injected. In contrast, continuous infusion of PTH stimulates bone resorption. PTH concentration may be affected by physical exercise and our review was designed to investigate this relationship. The variation in PTH concentration appears to be influenced by both exercise duration and intensity. There probably exists a stimulation threshold of exercise to alter PTH. PTH regulation is also influenced by the initial bone mineral content, age, gender, training state, and other hormonal and metabolic factors (catecholamines, lactic acid and calcium concentrations).